BRITISH ESPIONAGE IN AFGHANISTAN IN THE 19TH CENTURY - Riskulov Shakhjakhan Narmakhamatovich; Prof. J.Kh. Ismailova (Journals Park Publishing, 2023)
In this article, the objectives of spies, ambassadors and missions sent by the British East India Company to the territory of Afghanistan in the first half of the 19th century, their geopolitical activities in the region, the state structure of Afghanistan, the form of government, relations with neighboring countries, Afghanistan The topography of Afghanistan, the economic, political and social situation of the Afghan people, their customs, traditions, lifestyle, diversity of nationalities, the specific characteristics of this period are described. Also, at the end of the thirties of the 19th century, how the British colony carried out military-political and diplomatic preparations for the invasion of Afghanistan. what sources, political and economic conditions of the regions are carefully studied.
Keywords: Afghanistan, Sherali Khan, Central Asia, ambassadors, Ost-Indian company. Afghan, Afghan people, geopolitical, ambassadors, expeditions spies, Elfinstown, William Morkraft, A.Byorns, Charles Messon, Robert Lich, Kabul, Khirot, Beaver, Lake Vahan